Moyamoya Disease A Disease to Count On in Your Daily Practice - Vanaclocha, Vicente (IntechOpen, 2021)
Moyamoya disease is a rare cerebrovascular disease most prevalent in East Asian countries. Thanks to new diagnostic capabilities, the number of cases discovered, including asymptomatic patients, has been increasing steadily. However, asymptomatic from the clinical point of view does not necessarily mean that there are no subjacent problems. Indeed, many patients harbour cognitive decline long before they exhibit clinical or radiological manifestations. The only effective treatment is surgical revascularization, either direct, indirect, or combined. Many posit that preventive surgical treatment should be considered even in asymptomatic moyamoya patients, particularly in the paediatric age group. This book expands on these ideas and examines the various aspects of this dreadful disease.